Criminal Justice News (2016)
Criminology and Criminal Justice Students Present at 2016 CURIO Conference Dr. Posick and Dr. Brent Present at Annual D.I.F Conference Dr. Brent Awarded 2016 Faculty Research Committee Award Dr. Agnich and Dr. Brent Nominated for University Awards Mock Mediation Club Hosts First Tournament at Southern Criminal Justice and Criminology Faculty Publish their Researc